ASSOCIATION BETWEEN MAGNESIUM LEVELS AND THE SEVERITY OF ACNE VULGARIS - Tamara, Adelia; Anggowarsito, Jose L; Tandyono, Venny (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Acne vulgaris is a cosmetic problem that often occurs in 80% of the population, especially reproductive age (12-25 years). Acne vulgaris is a chronic inflammatory disease of pilosebaceous follicles with multifactorial causes and clinical manifestations of blackheads, papules, pustules, nodules, and cysts. Magnesium plays a role in increasing skin hydration, increasing skin permeability, barrier repair, and facilitating skin proliferation and epidermal differentiation to reduce inflammation. Hypomagnesium is thought to increase inflammation and affect androgen hormones, especially testosterone, which plays a role in increasing the hyperactivity of the sebaceous glands in the pathogenesis of Acne Vulgaris.Purpose: To determine the difference in magnesium levels in each severity degree of acne vulgaris, namely mild, moderate, and severe.Method: This study is an analytic observational study with a cross-sectional design. The sampling technique is purposive sampling with a total sample of 30 people. Data retrieval in this study was carried out using photo taking of three sides of the face (front, right oblique, left oblique). Then proceed with a three cc venous blood draw to measure magnesium levels in the blood.Results: This study found a significant difference between magnesium levels and the severity of acne vulgaris with a value of p = 0.032 (p <0.05). Magnesium levels in severe acne vulgaris were higher than moderate and mild acne vulgaris. However, magnesium levels in all samples were still within the normal range. There was a moderate positive correlation between the two variables with a p-value = 0.016 (p <0.05).Conclusion: There was a significant difference between magnesium levels and the severity of acne vulgaris, and there is a moderate positive correlation between magnesium levels and the severity of acne vulgaris, which means that the higher the magnesium level, the more severe the degree of acne vulgaris.